The Noctuoidea (Lepidoptera) from Cuba described by Herrich-Schäffer and Gundlach in the Gundlach Collection, Havana - Becker, Vitor Osmar (2002)
The taxonomic status of 94 nominal species of Noctuoidea from Cuba described by Herrich-Schäffer, and two species described by Gundlach is discussed. Type material of 49 nominal species preserved in Coll. Gundlach, Instituto de Ecologia y Sistemática, Havana, is evaluated. Seventy species names of Herrich-Schäffer and two of Gundlach are recognized, one genus name and 39 species names are synonymized, 16 new combinations, four reinstated synonyms and two species recalled from synonymy are established.